Genetic Variations rs859, rs4646, and rs372883 in the 3'-Untranslated Regions of Genes Are Associated with a Risk of IgA Nephropathy - Xiaohong Yang; Gang Jin; Yin Zhang; Maowei Xie; Wenning Li; Daofa Zhang; Ru Wang; Pei Zhang; Yeguang Han; Jiali Wei (Karger Publishers, 2019)
Background: Previous studies indicate that genetic factors play an important role in the pathogenesis of IgA nephropathy (IgAN). To evaluate the association between single nucleotide polymorphisms (SNPs) in the 3'-untranslated region (3'-UTR) of genes and IgAN risk, we performed a case-control study in a Chinese Han population. Materials: Twelve SNPs were selected and genotyped in 384 IgAN patients and 357 healthy controls. Odds ratio (OR) and 95% confidence intervals (CI) were calculated by logistic regression adjusted for age and gender. Multifactor dimensionality reduction (MDR) was used to analyze the interaction of SNP-SNP with IgAN risk. Results: Our study demonstrated that IL-16 rs859 (OR = 0.75, p = 0.040) and CYP19A1 rs4646 (OR = 2.58, p = 0.017) polymorphism were related to the risk of IgAN. In stratified analyses by gender, CYP19A1 rs4646 (OR = 2.96, p = 0.015) and BACH1 rs372883 (OR = 1.81, p = 0.038) polymorphisms conferred susceptibility to IgAN in males. Besides, rs372883 reduced IgAN risk in females (OR = 0.44, p = 0.042). We also found rs859 polymorphism was correlated with grade I-II (OR = 0.42, p = 0.028) in subgroup analysis of Lee's classification. Additionally, we found rs4646 polymorphism was correlated with serum creatinine (p = 0.035). Conclusion: Our results suggested that the IL-16 rs859, CYP19A1 rs4646, and BACH1 rs372883 polymorphisms have potential roles in the genetic susceptibility to IgAN in Chinese Han population.